Robert B. Parker's Ironhorse [large type] - Parker, Robert B., 1932-2010 (Parker, Robert B., 1932-2010. Cole and Hitch novel., 2013)
Newly appointed as territorial marshals, Virgil Cole and Everett Hitch step into a whirlwind of danger as they climb aboard a train traveling through the Indian Territories. A simple mission to escort Mexican prisoners to the border grows a lot more complicated when the Texas governor boards the train with his entourage and they must strive to fend off a pack of ruthless bandits.